Pain Experience during Initial Alignment with a Self-Ligating and a Conventional Fixed Orthodontic Appliance System: A Randomized Controlled Clinical Trial - Fleming, P. S.; DiBiase, A. T.; Sarri, G.; Lee, R. T. (The Angle orthodontist, 2009)
Objectives: To test the hypotheses that (1) there is no difference in the pain experience during the week following initial placement of two orthodontic appliances (SmartClip™ and Victory™; 3M Unitek, Monrovia, Calif); and (2) there is no difference in the pain experience during removal and insertion of orthodontic archwires with these brackets. Materials and Methods: Sixty-six consecutive patients were treated with a self-ligating bracket system (SmartClip™) or a conventional appliance (Victory™) on the basis of computer-generated random allocation. After appliance placement and engagement of a 0.016″ nickel-titanium archwire, pain experience was recorded after 4, 24, and 72 hours and after 7 days with the use of a visual analog system (VAS) questionnaire. At a subsequent visit, participants documented pain experiences during removal and insertion of 0.019 × 0.025″ archwires on an additional 100 mm VAS questionnaire. Independent t -tests and analyses of covariance were used to analyze normally distributed data; the Mann-Whitney U -test was used for skewed distributions. Results: Forty-eight (72.2%) and fifty-one (77.3%) subjects completed the first and second parts of the study, respectively. Bracket type had no influence on pain experience at 4 hours ( P = .958), 24 hours ( P = .289), 72 hours ( P = .569), and 7 days ( P = .756) following appliance placement. However, bracket type significantly influenced pain experience during archwire removal ( P = .001) and insertion ( P = .013). Conclusions: Hypothesis 1 cannot be rejected. The bracket type had no effect on subjective pain experience during the first week after initial placement of two preadjusted orthodontic appliances. Hypothesis 2 was rejected. Significantly greater discomfort was experienced during archwire insertion and removal with the SmartClip™ appliance.